ANALISIS RENTABILITAS PADA PT. CIPUTRA SURYA TBK TAHUN 2008-2012 - Desi Harsati (JURNAL MANAJEMEN, 2013)
This study aims to determine the profitability and how the effectiveness of the use of assets. Subjects were PT Ciputra Surya Tbk. Object of this research is earnings PT. Ciputra Surya Tbk from 2008-2012. Data analysis techniques used in this research is the analysis of the ratio of dupont analysis, commonsize analysis and activity ratios. The results showed that the development that occurs tends to increase profitability. From commonsize analysis increase profit margins are relatively small due to the element of cost of sales is still less efficient. And for the effectiveness of the use of assets as indicated by the turnover of the Operating Assets and arguably less effective management of its assets primarily in cash and receivables.